Workload Analysis with Full Time Equivalent Method to Optimize Production Unit Performance at PT X - Santika Sari; Farah Fauzia Imron; Nurfajriah Nurfajriah; Fajar Rahayu I.M (Journal of Integrated System, 2022)
PT X is one of the companies in the manufacturing industry engaged in the automotive sector. In carrying out the production process, PT X sometimes has problems, namely there is often a mismatch in the number of spare parts sent with the number of spare parts written on the purchase order (PO). The production delay occurred due to a shortage of manpower and an uneven workload in production activities at PT X. For this reason, it is necessary to measure the workload as a basis for calculating the workforce needs. In this study, researchers used the full time equivalent (FTE) method. After calculating with this method, it is known that the workload in the coated spare parts production line is not balanced among 10 operators who work, where 3 operators with high workloads or overload, 5 operators with normal workloads, and 2 operators with low workloads or underload. The results of the calculation show that the workload has a negative effect on operator performance. The proposed improvement is by adding 2 operators and mutating horizontally, the results obtained are an optimal workforce of 12 people, with workloads in the normal and low (underload) categories.